The Mystery of the Fall of the Abbasid Dinasty: Internal Conflicts and attacks that Shattered the Great Caliphate - Muhammad Ridwan; Banjarnaor, Riadi; Roza, Ellya (Faculty of Ushuluddin, Adab, and Humanities Universitas Islam Negeri Salatiga, 2024)
The Abbasid Dynasty, founded by Abu Abbas al-Shaffah in 750 AD, played a significant role in the history of Islamic civilization. Replacing the Umayyad Dynasty, it marked the Islamic Golden Age, integrating various cultures and advancing knowledge, the economy, and civilization. However, the dynasty faced numerous challenges, including internal conflicts, a monarchical political system, and power struggles within the family, which led to instability and civil wars. This research was conducted using a library research method, with a qualitative approach and continued with content analysis., shows that the Abbasid Dynasty symbolized the rise of Islam and its advancements but was also entangled in internal conflicts and political weaknesses. Their downfall was accelerated by the emergence of smaller kingdoms and external threats, such as the Mongol invasion that destroyed Baghdad. The experience of the Abbasid Dynasty highlights the dangers of power without wisdom and justice, emphasizing the importance of humane leadership.